Pengaruh Edukasi Kesehatan tentang SADARI terhadap Pengetahuan dan Keterampilan Siswi di Sekolah Mambaul Hikam Desa Tegal Mojo Kabupaten Probolinggo - Aisyah, Siti; Andayani, Sri Astutik; J.A.H, Maulidiyah (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2024)
Breast cancer remains one of the leading causes of death among women, often due to late detection. Early detection can be achieved through Breast Self-Examination (BSE), which helps identify abnormalities early. This study examines the impact of health education about BSE on the knowledge and skills of female students at Mambaul Hikam School, Tegal Mojo, Probolinggo. A quasi-experimental design was used with pretest-posttest groups. The population comprised 115 students, and 90 respondents were selected through probability sampling using the simple random sampling method. Data were collected using questionnaires and observation checklists and analyzed with Wilcoxon and Mann-Whitney tests. The findings show a significant increase in knowledge and skills in the intervention group after health education (p = 0.000), highlighting the effectiveness of BSE education in improving early detection capabilities among students. This study emphasizes the importance of structured health education to enhance knowledge and skills for early breast cancer detection.